Thermoelectric Generators Applied as a Power Source in CubeSats: State of the Art - Gabriel Brugues Soares; Jorge Javier Gimenez Ledesma; Eder Andrade da Silva; Oswaldo Hideo Ando Junior (Energies)
This systematic review outlines the application of thermoelectric generators (TEGs) as energy sources in CubeSats. While CubeSats currently rely on solar cells with efficiencies between 16.8% and 32.2%, their performance diminishes with increased distance from the Sun. TEGs, although used in radioisotope thermoelectric generators (RTGs) for satellites, remain underutilized in CubeSats. A literature review revealed 33 relevant articles, with 21.2% employing simulation software to evaluate thermal behavior. Among 34 patents, only one mentioned micro-TEGs, with most focusing on structural improvements. Patent activity peaked between 2016 and 2020, emphasizing structural and thermal optimization, but no patents addressed TEGs as energy sources for CubeSats, highlighting a significant research gap. TEGs present a viable solution for harnessing residual heat in CubeSats.